A prospective investigation of perceived stress, infertility‐related stress, and cortisol levels in women undergoing in vitro fertilization: influence on embryo quality and clinical pregnancy rate. (10th January 2018) - Cesta, Carolyn E.; Johansson, Anna L.V.; Hreinsson, Julius; Rodriguez‐Wallberg, Kenny A.; Olofsson, Jan I.; Holte, Jan; Wramsby, Håkan; Wramsby, Margareta; Cnattingius, Sven; Skalkidou, Alkistis; Nyman Iliadou, Anastasia
Abstract: Introduction: Women undergoing fertility treatment experience high levels of stress. However, it remains uncertain if and how stress influences in vitro fertilization (IVF) cycle outcome. This study aimed to investigate whether self‐reported perceived and infertility‐related stress and cortisol levels were associated with IVF cycle outcomes. Material and methods: A prospective cohort of 485 women receiving fertility treatment was recruited from September 2011 to December 2013 and followed until December 2014. Data were collected by online questionnaire prior to IVF start and from clinical charts. Salivary cortisol levels were measured. Associations between stress and cycle outcomes (clinical pregnancy and indicators of oocyte and embryo quality) were measured by logistic or linear regression, adjusted for age, body mass index, education, smoking, alcohol and caffeine consumption, shiftwork and night work. Results: Ultrasound verified pregnancy rate was 26.6% overall per cycle started and 32.9% per embryo transfer. Stress measures were not associated with clinical pregnancy: when compared with the lowest categories, the adjusted odds ratio (OR) and 95% confidence interval (CI) for the highest categories of the perceived stress score was 1.04 (95% CI 0.58–1.87), infertility‐related stress score was OR = 1.18 (95% CI 0.56–2.47), morning and evening cortisol was OR = 1.18 (95% CI 0.60–2.29) and OR = 0.66 (95% CI 0.34–1.30), respectively. Conclusions: Perceived stress, infertility‐related stress, and cortisol levels were not associated with IVF cycle outcomes. These findings are potentially reassuring to women undergoing fertility treatment with concerns about the influence of stress on their treatment outcome.